A Study on Asset Liability Management of Scheduled Commercial Banks in India - Mathiraj, S. P.; Ramya , V. (Gyan Management Journal, 2013)
Asset liability management is a significant task for banks and financial institutions because of volatile global financial markets, propagation of new financial products and changing regulatory environments. Asset-liability management of commercial banks may be defined as the concurrent development of all asset and liability position on the bank’s balance sheet under deliberation of the different bank management objectives and lawful, managerial and market constraints,for the purpose of the enhancing the value of the bank, providing liquidity, and extenuating interest rate risk. Scheduled commercial bank in India plays a significant role in the distribution of credit and mobilization of deposits. This study has been carried to test the logic behind in the management of assets and liabilities of Indian scheduled commercial banks. Public sector banks, private sector banks, foreign banks are considered for the study. Three financial years starting from 2009 to 2011 have been selected and all banks balance sheet are analyzed for the sample period. In order to know the quantum of asset liability management canonical correlation analysis has been performed, redundancy factors show the effective management of assets or liabilities. This study concluded that all scheduled banks are effectively manages its assets and liability management is dependent to the asset management.